Modulation of fibroblast growth factor-2 receptor binding, dimerization, signaling, and angiogenic activity by a synthetic heparin-mimicking polyanionic compound. - Miao, H Q (1997)
Heparan sulfate (HS) proteoglycans play a key role in cell proliferation induced by basic fibroblast growth factor (FGF-2) and other heparin-binding growth factors. To modulate the involvement of HS, we have used a synthetic, nonsulfated polyanionic aromatic compound (RG-13577) that mimics functional features of heparin/HS. FGF-2-stimulated proliferation of vascular endothelial cells was markedly inhibited in the presence of 5-10 microg/ml compound RG-13577 (poly-4-hydroxyphenoxy acetic acid; Mr approximately 5 kD). Direct interaction between RG-13577 and FGF-2 was demonstrated by the ability of the former to compete with heparin on binding to FGF-2. RG-13577 inhibited FGF-2 binding to soluble- and cell surface-FGF receptor 1 (FGFR1). Unlike heparin, RG-13577 alone failed to mediate dimerization of FGF-2. Moreover, it abrogated heparin-mediated dimerization of FGF-2 and FGFR1, as well as FGF-2 mitogenic activity in HS-deficient F32 lymphoid cells. The antiproliferative effect of compound RG-13577 was associated with abrogation of FGF-2-induced tyrosine phosphorylation of FGFR1 and of cytoplasmic proteins involved in FGF-2 signal transduction, such as p90 and mitogen-activated protein kinase. A more effective inhibition of tyrosine phosphorylation was obtained after removal of the cell surface HS by heparinase. In contrast, tyrosine phosphorylation of an approximately 200-kD protein was stimulated by RG-13577, but not by heparin or FGF-2. RG-13577 prevented microvessel outgrowth from rat aortic rings embedded in a collagen gel. Development of nontoxic polyanionic compounds may provide an effective strategy to inhibit FGF-2-induced cell proliferation associated with angiogenesis, arteriosclerosis, and restenosis.